2013
DOI: 10.1177/1740774513495984
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility trial of a Spanish-language multimedia educational intervention

Abstract: Background Hispanic cancer patients are underrepresented in clinical trials (CTs). Research suggests lack of knowledge and language barriers contribute to low accrual. Audiovisual materials offer advantages to Hispanic populations because they have high acceptability; are easy to disseminate; and can be viewed with family. Purpose Hispanic cancer patients and caregivers participated in focus groups to aid in developing a Spanish language audiovisual intervention. This project explored the feasibility of deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
(64 reference statements)
0
14
0
Order By: Relevance
“…When developing our novel framework, we found that the interventions included in our synthetic analysis leveraged a broad range of behavioral strategies beyond financial incentives to boost research participant engagement. Strategies ranged from establishing relationships with research participants through case managers 25 and lay advocates 26 to changing the way that research teams engaged participants, which included leveraging different communication methods—for example, text messaging, 27 phone calls, 28 websites, 29 and video 30 —or locations, such as recruiting in churches. 31 Some strategies influenced the social context in which potential research participants made decisions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…When developing our novel framework, we found that the interventions included in our synthetic analysis leveraged a broad range of behavioral strategies beyond financial incentives to boost research participant engagement. Strategies ranged from establishing relationships with research participants through case managers 25 and lay advocates 26 to changing the way that research teams engaged participants, which included leveraging different communication methods—for example, text messaging, 27 phone calls, 28 websites, 29 and video 30 —or locations, such as recruiting in churches. 31 Some strategies influenced the social context in which potential research participants made decisions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While most research to date has focused on English-speaking patients, there is growing evidence that this approach may also benefit both English and nonEnglish speaking CALD groups. 33,34 The electronic delivery of multimedia trial information has additional advantages for working with CALD patients, such as being customizable to multiple languages and able to simultaneously deliver information and assess comprehension.…”
Section: Strategies To Improve Cald Patient Trial Participationmentioning
confidence: 99%
“…A first step to achieving this goal involves linguistic translation and transcreation. More broadly, health promotion messages are more effective when they undergo a process of transcreation and are made available in the target audience's language (Wells et al 2013). Transcreation goes beyond the linguistic translation of materials; its purpose is to conceptually recreate the text to meet the informational needs of the target population by including culturally relevant terminology, images, or themes (Simmons et al 2011;Solomon et al 2005).…”
Section: Introductionmentioning
confidence: 99%